IMPOLITENESS IN TANJUNG AGUNG TRADITIONAL MARKET - Afrilesa, Rini; Untari, Jelita; Putri Kh. R. A, Merdeka; Rina, Rina (Universitas Muara Bungo, 2023)
This research investigates linguistic impoliteness used in Tanjung Agung Traditional Market through the examination of impoliteness strategies proposed by Jonathan Culpeper. It examines how impoliteness are used on the traditional market of Tanjung Agung Village. The research uses descriptive qualitative method. First, The writer found that people in the market sometime use impoliteness strategis in daily life, usually can be in the Market. It can be happen between the buyers and sellers conversation to express the negative attitude in the Traditional market. Second, the writers found that four out of the impoliteness in Tanjung Agung Traditional Market